The day the world stopped turning - Morpurgo, Michael (Feiwel and Friends, 2019)
Two young friends find themselves entrapped by the circumstances of WWII when German soldiers enter their French community. The young girl, Kezia, deals with the prejudice of others because of her Roma decent. While her friend, Lorenzo, is looked down upon because of his autism. As they struggle through the frightening time, a German soldier shows unexpected compassion to them even while he must follow orders that could threaten everything they care about.